Mutual regulation between β-TRCP mediated REST protein degradation and Kv1.3 expression controls vascular smooth muscle cell phenotype switch. (November 2020) - Ye, Meng; Guo, Xiangjiang; Wang, Han; Wang, Yuli; Qian, Xin; Deng, Haoyu; Wang, Weilun; Yang, Shuofei; Ni, Qihong; Chen, Jiaquan; Lv, Lei; Zhao, Yiping; et al.
Abstract: Background and aims: Phenotypic switch of vascular smooth muscle cells (VSMC) plays a key role in the pathogenesis of atherosclerosis and restenosis after artery intervention. Transcription repressor element 1-silencing transcription factor (REST) has been identified as key regulator of VSMC proliferation. In the present study, we sought to investigate the potential association of E3-ubiquitin ligase β-TRCP mediated REST protein degradation with Kv1.3 expression during VSMC phenotypic switch. Methods: Protein and mRNA expression was measured in ex vivo and in vitro models. Protein interaction and ubiquitination were analyzed by immunoprecipitation assays. ChIP assays were performed to assess the relationship between REST and targeted DNA binding site. Results: We found that the expression level of E3-ubiquitin ligase β-TRCP is significantly increased during VSMC phenotypic switch. REST protein ubiquitination mediated by β-TRCP is critical for VSMC proliferation and migration. We also found that the gene KCNA3 encoding potassium channel protein Kv1.3 contains a functional REST binding site and is repressed by REST. Downregulation of REST by β-TRCP and consequently upregulation of Kv1.3 are important events during VSMC phenotypic switch. Furthermore, upregulated Kv1.3 accelerates β-TRCP modulated REST degradation through Erk1/2 signaling. Conclusions: Our results reveal a fundamental role for regulatory interactions between β-TRCP modulated REST degradation and Kv1.3 in the control of the multilayered regulatory programs required for VSMC phenotype switch. Graphical abstract: Image 1 Highlights: Expression levels of E3-ubiquitin ligase β-TRCP are significantly increased during VSMC phenotypic switch. REST protein ubiquitination mediated by β-TRCP is critical for VSMC proliferation and migration. The KCNA3 gene encoding potassium channel protein Kv1.3 contains a functional REST binding site and is repressed by REST. Downregulated REST by β-TRCP and upregulated Kv1.3 are important events during VSMC phenotypic switch. Upregulated Kv1.3 accelerates β-TRCP modulated REST degradation through Erk1/2 signaling.